Preliminary investigation into surface finish and damage when grinding silicon carbide - Konneh, Mohamed (s.n, 2012)
This research project was undertaken to study and assess the surface finish and integrity of the silicon carbide (SiC) work piece and tool wear after the machining process, using 2mm-diameter diamond coated end mills. In this experimental research, independent machining parameters considered are depth of cut 10-50um, feed rate 6-14mm/min and the spindle speed 50,000-70,000 rpm and the dependent variable considered are surface roughness (um), surface morphology and tool wear